Gold nanoparticles antibacterial activity: Does the surface matter? - Saed, Marwan; Ayivi, Raphael D.; Wei, Jianjun; Obare, Sherine O. (Colloid and interface science communications, 2024)
The misuse and overuse of antibiotics have ushered in the rapid rise of antimicrobial resistance (AMR). Gold nanoparticles (AuNPs) are considered a potential solution for AMR due to their dual role as antibacterial agents and antibiotic-delivery vehicles. AuNPs with varied surface area, charge, and morphology have been utilized alone and with antibiotics tailored on their surface to overcome resistant bacteria. However, transitioning AuNPs from lab to bedside faces challenges due to the inconsistent antibacterial outcomes and the need for a consensus on the optimal AuNP features that harness their potential as antibacterial agents. This review navigates through the interplay of AuNPs' surface and their antibacterial behavior, considering their surface charge, surface potential, surface coating, surface area, morphology, and antibiotic functionalization. Our review serves as a guide for AuNPs surface features that elicit the most favorable antibacterial outcomes, which will aid in formulating a novel antibacterial agent capable of counteracting AMR. [Display omitted] •AuNPs as a promising solution for multi-drug resistant bacteria.•The surface properties of AuNPs influence the antibacterial outcome.•Surface charge and Zeta potential determine the antibacterial behavior of AuNPs.•AuNPs' size and shape play a key role in their antibacterial activity.•Antibiotic-functionalized AuNPs can be the next magic bullet for AMR.